The Effect Of Product Quality And Price On The Purchase Decision Of A Toyota Raize Brand Car At The Toyota Auto 2000 Lahat Dealer - Yovi Kharisma; Amaludin Amaludin; Tri Rusilawati Kasisariah (Universitas Dehasen Bengkulu, 2026)
This study aims to determine how the influence of Product Quality and Price partially and simultaneously influence the purchasing decision of Toyota Raize brand cars at Toyota Auto 2000 Lahat Dealer. The sample in this study was 39 respondents. The sampling method used by the researcher was Incidental sampling. This type of research is quantitative research using multiple linear regression analysis techniques processed using the SPSS application and produces a regression equation . The results of this study are: there is a significant influence between Product Quality on the purchasing decision of Toyota Raize brand cars at Toyota Auto 2000 Lahat Dealer, there is a significant influence between Price on the purchasing decision of Honda brand motorbikes at Bintang Motor Lahat dealer. The F test shows that Product Quality and Price have a simultaneous influence on the purchasing decision of Toyota Raize brand cars at Toyota Auto 2000 Lahat Dealer.